2019
DOI: 10.4236/health.2019.1110110
|View full text |Cite
|
Sign up to set email alerts
|

A Weight-Loss and Healthy Living Program for Men Delivered in Swedish Football and Ice-Hockey Clubs (ViSiT): Results from the ViSiT Feasibility Study

Abstract: Background: Men appear less interested than women in engaging in healthpromoting programs. We investigated the feasibility and proof of concept of a novel intervention program targeting male supporters of professional sports clubs. Methods: Our intervention is called ViSiT and the target population in this study was overweight male supporters aged 35-65 years with a body mass index ≥ 28 kg/m 2 , recruited through one football and one ice-hockey club. The participants (n = 22) participated in a 12-week lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a review of 31 intervention programs to promote physical activity for adult men, including FFIT studies, it was concluded that all studies using professional clubs to recruit men resulted in increased physical activity (Bottorff et al, 2015). Further, the ViSiT program resulted in clinically relevant weight reduction for the participants (Leijon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of 31 intervention programs to promote physical activity for adult men, including FFIT studies, it was concluded that all studies using professional clubs to recruit men resulted in increased physical activity (Bottorff et al, 2015). Further, the ViSiT program resulted in clinically relevant weight reduction for the participants (Leijon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The attendance rate in ViSiT was high for more information see (Leijon et al, 2019). and the participants mentioned that they did not want to miss any of the sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation